Carol L. Lawton. The Athenian Agora XXXVIII: Votive Reliefs. pp. 248, with 12 col. ills, 3 col. and b/w plans, 60 plates. ISBN: 978-0-87661-238-5, hardcover £130. - Fullerton, Mark (Journal of Greek Archaeology, 2020)
This beautiful volume is more than up to the high standard of Agora sculpture publications, first set by Evelyn Harrison’s study of Roman portraits (Agora v.1, 1953), which appeared some 66 years ago. This, the latest volume to appear in the Agora series, is the fourth devoted to sculpture, following Harrison’s on Archaic and Archaistic Sculpture (v.11, 1965) and that on Funerary Sculpture (v.35, 2013) by Laura Grossman. The Classical and Hellenistic sculpture is currently under intensive study by Andrew Stewart, who has produced a series of stimulating articles in Hesperia on free-standing and especially architectural sculpture, adding to our understanding of the Hephaisteion and, currently, bringing lesser-known buildings like the Temple of Ares to life by identifying substantial portions of its sculptured adornment.